PELATIHAN HATHA YOGA DALAM MENINGKATKAN DAYA TAHAN KARDIOVASKULER PADA SISWI USIA 16 – 18 TAHUN DI SMA NEGERI 3 DENPASAR - I Gusti Ayu Dwita Wahyu Laksmi; Anak Ayu Nyoman Trisna Narta Dewi; I Wayan Sugiritama (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACTCardiovascular endurance is the ability to perform an activity with a long time without experiencing fatigue. Thepurpose of this research is to know the effect of the increase in the hatha yoga exercise in improving cardiovascularendurance. This research is experimental research using the design of One Group Pre Test and Post Test Design.Sampling techniques in this research is consecutive sampling. Sample research totalling sixteen people given hathayoga exercise. The exercises were done for 12 weeks with frequency of three times a week in SMA Negeri 3 Denpasar.Data collection is done by measuring cardiovascular endurance by using the cooper 2,4 kilometers test before and afterthe training.The result using Paired Sample T-test obtainable results showed p = 0,000 < 0,05, so it can be concluded thathatha yoga exercises in increasing cardiovascular endurance.Keyword: Cardiovascular Endurance, Hatha Yoga Exercises, Female Student